If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3x + -3) = 3(4x + -4) Reorder the terms: 4(-3 + 3x) = 3(4x + -4) (-3 * 4 + 3x * 4) = 3(4x + -4) (-12 + 12x) = 3(4x + -4) Reorder the terms: -12 + 12x = 3(-4 + 4x) -12 + 12x = (-4 * 3 + 4x * 3) -12 + 12x = (-12 + 12x) Add '12' to each side of the equation. -12 + 12 + 12x = -12 + 12 + 12x Combine like terms: -12 + 12 = 0 0 + 12x = -12 + 12 + 12x 12x = -12 + 12 + 12x Combine like terms: -12 + 12 = 0 12x = 0 + 12x 12x = 12x Add '-12x' to each side of the equation. 12x + -12x = 12x + -12x Combine like terms: 12x + -12x = 0 0 = 12x + -12x Combine like terms: 12x + -12x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 3z+2(4x-2)=5(3-2) | | (8x^2-4x+14)+(-7x^2+3x-10)= | | 6x=2(4x+5) | | 3(4x+-5)=9 | | 3(4+-5)=9 | | 7c+-15=-2(6(c+-3)+-4(2+-1c)) | | 6x-3(2x-1)=6(-2+1)-3x | | 2x=180-7x | | 45=k(9)(5) | | -9p=-2 | | 4.9=7.3-0.6x | | a^2bc+ab^2c+abc^2=0 | | m^2+19m+48= | | X(x+81)=0 | | 8-2w^2=0 | | 5p-5q=-12 | | 4.9x+5=3.9x | | 10+8=-2(5x-9) | | 7x+9-6x=13 | | -20x=-4x-6 | | 2(x-3)=-h+3(h+6) | | 13-20= | | -14+1= | | v^2+2v-25=0 | | 2s^2=25 | | 150+110+450+x=1000 | | 4w+19=-7(w-9) | | X-6-25x^(1/2) | | 7+x+1=6x | | -14+26=-2(x+5) | | 7x-8(2x-3)=2(3x-9)-5x | | -10y+3y= |